Development of Critical Thinking in Pharmacy Education - Michael J Peeters; Kimberly L Zitko; Kimberly A Schmude (University of Minnesota Libraries Publishing, 2016)
The concept of development is ubiquitous throughout higher education. Development of critical thinking, problem-solving, and clinical reasoning are noted as important outcomes in higher education, including health professions education. In this era of widening scrutiny, demonstration of this outcome within programmatic assessment is becoming increasingly important. Programmatic assessment of critical thinking is complicated because of its multiple definitions, array of theoretical frameworks, and variety of measurement instruments. Additionally, recent guidelines and standards for pharmacy education have affirmed "habits of mind," which are not new to education and encompass analytical critical thinking. In this paper, we sought to provide: 1) an overview of various critical thinking measurement instruments with their different associated critical thinking definitions, 2) a background and framework for thinking using the Dimensions of Learning model, 3) implications and applications for assessing cognitive development (critical and complex thinking) within the context of pharmacy education, and 4) specific suggestions for assessment in pharmacy education.   Type: Idea Paper